Arizona goes to war : the home front and the front lines during World War II - Melton, Brad, 1971-; Smith, Dean, 1923-2012 (Book collections on Project MUSE., 2003)
"It was a cold gray morning in northeast France when Pfc. Silvestre Herrera's unit came under heavy fire from a Nazi artillery barrage. Armed with only a hand grenade and his M1 rifle. Herreta fixed his bayonet and mounted a one-man charge, single-handedly capturing eight German soldiers, then killing two more and pinning down the enemy despite having had both feet blown off by a mine.